A participação e a gestão democrática no programa nacional de fortalecimento dos conselhos escolares - Moraes, Aline C. A. (2017)
This article aims to analyze the concept of participation and democratic management disseminated through the National Program for the Strengthening of School Boards (PNFCE) and discuss the importance of strengthening the board. In the survey we used as methodological resources to documentary research in instructional booklets prepared by the MEC / SEB; bibliographical research and analysis in reports of "successful experiences" of schools that have adopted such a program. In this paper, at first we present the design of school boards and discuss the political process that led to the insertion of this collegiate educational policies, specifically in LDBEN 9394/96. Following is an analysis about the concept of democratic management of the National Program for the Strengthening of School Boards, showing that it constitutes a process that calls to be made effective organizational and political changes in society. We conclude that the concept of democratic management and participation, disseminated by PNFCE is guided in the logic of policies for widespread education after the 1990s, in which the partnership between school and community is seen as a condition without which it is not possible to achieve quality in school. But we must question about this redemptive design and also on the concrete and objective conditions before which the democratic management is effective